Sudden cardiac death while waiting: do we need the wearable cardioverter-defibrillator? - Israel, Carsten W.; Staudacher, Ingo; Leclercq, Christophe; Botto, Giovanni Luca; Scherr, Daniel; Fach, Andreas; Duru, Firat; Zylla, Maura Magdalena; Katus, Hugo; Thomas, Dierk (Clinical research in cardiology, 2022)
Sudden cardiac death (SCD) is the most frequent cause of cardiovascular death in industrialized nations. Patients with cardiomyopathy are at increased risk for SCD and may benefit from an implantable cardioverter-defibrillator (ICD). The risk of SCD is highest in the first months after myocardial infarction or first diagnosis of severe non-ischemic cardiomyopathy. On the other hand, left ventricular function may improve in a subset of patients to such an extent that an ICD might no longer be needed. To offer protection from a transient risk of SCD, the wearable cardioverter-defibrillator (WCD) is available. Results of the first randomized clinical trial investigating the role of the WCD after myocardial infarction were recently published. This review is intended to provide insight into data from the VEST trial, and to put these into perspective with studies and clinical experience. As a non-invasive, temporary therapy, the WCD may offer advantages over early ICD implantation. However, recent data demonstrate that patient compliance and education play a crucial role in this new concept of preventing SCD.
Gesehen am 25.09.2024